2003
DOI: 10.1088/0305-4470/36/23/105
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Gaussian wave packet and nonadiabatic geometrical phase for the time-dependent singular oscillator

Abstract: The geometrical phase of a time-dependent singular oscillator is obtained in the framework of Gaussian wave packet. It is shown by a simple geometrical approach that the geometrical phase is connected to the classical Explicitly time-dependent problems present special difficulties in classical and quantum mechanics. However, they deserve detailed study because very interesting properties emerge when, even for simple linear systems, some parameters are allowed to vary with time. For instance, particular recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…However, they deserve detailed study because very interesting properties emerge when, even for simple linear systems, some parameters are allowed to vary with time. For instance, particular recent interest has been devoted to the Schrödinger equation for timedependent potentials, mainly variable mass and frequency harmonic oscillators [1][2][3][4][5][6][7][8][9][10][11][12][13]. Besides the harmonic-oscillator potential model, the time-dependent linear potential has been frequently used in some others studies [14][15][16][17].…”
mentioning
confidence: 99%
“…However, they deserve detailed study because very interesting properties emerge when, even for simple linear systems, some parameters are allowed to vary with time. For instance, particular recent interest has been devoted to the Schrödinger equation for timedependent potentials, mainly variable mass and frequency harmonic oscillators [1][2][3][4][5][6][7][8][9][10][11][12][13]. Besides the harmonic-oscillator potential model, the time-dependent linear potential has been frequently used in some others studies [14][15][16][17].…”
mentioning
confidence: 99%
“…Hence the system is a kind of TDHSs that have attracted wide interest in the physical society [5,6,[17][18][19][20][21][22][23][24][25][26]. To derive quantum solutions of a TDHS, it is convenient to introduce an invariant operator [5,6] because the quantum properties of such system can be investigated via the eigenstates of the invariant operator.…”
Section: Invariant Operator and Quantum Solutionsmentioning
confidence: 99%
“…A relationship between the quantum geometric phase and the classical Hannay angle has been found by Maamache and Bekkar. [1] Kim et al showed that the dispersions of quantum states do not depend on external forces. [2] A solution of the Schrödinger equation for a timedependent Hamiltonian system (TDHS) was obtained by Abdalla and Choi [3] and de Lima et al [4] using linear invariants and quadratic invariants.…”
Section: Introductionmentioning
confidence: 99%